Acute and chronic weight-making practice in professional mixed martial arts athletes: an analysis of 33 athletes across 80 fights - Reale, R.; Wang, J.; Hu Stull, C.; French, D.; Amasinger, D.; Wang, R. (International Journal of Sport Nutrition and Exercise Metabolism, 2024)
Mixed martial arts` popularity has increased in recent years, alongside descriptive research and evidence-based performance recommendations. Guidelines for (both chronic and acute) weight making exist; however, how these translate in real-life scenarios and detailed investigations on practices in larger groups deserve attention. The present study examined the body mass (BM) and composition of 33 professional mixed martial arts athletes preparing for 80 fights. Athletes were supported by on-site dietitians, who encouraged evidence-based practices. Fasted BM was measured throughout the last ~10 days before all bouts (acute weight management phase). A subset of athletes had body composition assessed before and after the chronic weight loss phase for 40 fights. Most athletes engaged in chronic BM loss, and all engaged in acute weight loss. Many lost fat-free mass (FFM) during the chronic phase, with rates of BM loss <0.5% best preserving FFM. Regardless of losses, the present athletes possessed greater FFM than other combat sport athletes and engaged in greater acute weight loss. Dehydration in the 24-48 hr before the weigh-in was not reflective of weight regain after the weigh-in, rather BM 7-10 days before the weigh-in was most reflective. These findings suggest that many mixed martial arts athletes could increase FFM at the time of competition by maintaining leaner physiques outside of competition and/or allowing increased time to reduce BM chronically. Acutely, athletes can utilize evidence-based protocols, eliminating carbohydrates, fiber, sodium, and finally fluid in a staged approach, before the weigh-in, reducing the amount of sweating required, thus theoretically better protecting health and preserving performance.